ӨНДИРИСТИ БАСҚАРЫЎДЫҢ БИР ҲӘМ ЕКИ ЭТАПЛЫ СТОХАСТИКАЛЫҚ ТРАНСПОРТ МӘСЕЛЕЛЕРИН ШЕШИЎДИҢ ПРОГРАММАЛЫҚ ТӘМИЙНАТЫН ИСЛЕП ШЫҒЫЎ - Утеулиев, Н.У.; Орынбаев, А.Б.; Махамбетов, П.Ж.; Мамутова, А.К. (SCIENCE and SOCIETY, 2021)
This article discusses the problem of creating software in the C# programming in the Microsoft Visual Studio 2017 Environment on the algorithms for solving one-and two-stage stochastic transport issues of functional mining.